Pelatihan Penyusunan Proposal Penelitian Tindakan Kelas Untuk Meningkatkan Kompetensi Profesional Guru MTs Negeri 3 Ende - Melkyanus Bili Umbu Kaleka; Hamsa Doa; Ilyas Ilyas; Yulius Saprianus Dala Ngapa; Richardo Barry Astro; Yasinta Embu Ika (Jurnal Pengabdian UNDIKMA, 2022)
The purpose of this training activity is so that the teachers of MTsN 3 Ende can prepare proposals for Classroom Action Research, carry out Classroom Action Research, and can also report the results of Classroom Action Research. The method of activity in the form of training consists of 3 stages, namely planning, implementation and evaluation. The target of the service is all 20 MTsN 3 teachers. The evaluation instrument is using test questions and performance. The test was given to determine the teacher's understanding of the basic concepts and procedures for implementing Classroom Action Research. The results of the implementation of service activities for teachers at MTsN 3 Ende are included in the quite successful category with an average success of 60%. Thus, the implication of this training activity is that it is able to provide good results for increasing the competence of teachers' professionalism.